2021
DOI: 10.3390/medicina57020146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Food-Hypersensitivity and Food-Dependent Anaphylaxis in Colombian Schoolchildren by Parent-Report

Abstract: Background and objectives: The epidemiology of food allergy (FA) and food-dependent anaphylaxis remains unknown in Colombia. Our aim was to estimate by parent-report the prevalence of FA and food-dependent anaphylaxis in a Colombian population of schoolchildren. Materials and methods: A printed questionnaire was sent to parents of schoolchildren aged 5–12 years old from Medellín, Colombia in order to collect FA-related data. Results: Nine hundred and sixty-nine (969) parents returned the questionnaire with val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Estimated fruit allergy prevalence ranges between 0.029% and 8% [1,8,10,[12][13][14]18,19,21,24,25,27,[30][31][32][33]35]. Ahanchian et al and Lee et al reported the number of fruit allergic cases as 371 and 26, respectively, without providing the total study population [11,16].…”
Section: Global Prevalence Of Fruit Allergymentioning
confidence: 99%
“…Estimated fruit allergy prevalence ranges between 0.029% and 8% [1,8,10,[12][13][14]18,19,21,24,25,27,[30][31][32][33]35]. Ahanchian et al and Lee et al reported the number of fruit allergic cases as 371 and 26, respectively, without providing the total study population [11,16].…”
Section: Global Prevalence Of Fruit Allergymentioning
confidence: 99%
“…The individuals were classified as follows [11,12,15]: (1) Parent-reported physiciandiagnosed food allergy (PR-PD FA), preschoolers whose parents reported medical diagnosis of food allergy; (2) "Immediate-type FA, ever", preschoolers whose parents reported recurrent and convincing symptoms of immediate-type food allergy; (3) "Immediate-type FA, current", preschoolers that met criteria for "immediate-type FA, ever", but whose parents reported that, currently, their children are unable to eat the suspect food without triggering any reaction; (4) "Food-dependent anaphylaxis", according to [15].…”
Section: Classification Of Individualsmentioning
confidence: 99%
“…These aspects motivate researchers to carry out prevalence studies in specific regions of Latin American countries to characterize the main foods causing allergies in different age groups and to know the magnitude and relevance of the problem. Although there is still limited information [10], most food allergy epidemiological studies carried out in Latin America have been focused on schoolchildren, informing prevalence rates between 1.4 and 5.5% [11][12][13][14][15]. In Mexico, the second-largest Latin American country in terms of population and the third in territorial extension [16], only one food allergy prevalence study has been conducted in preschoolers, which took place in the west of the country [17].…”
Section: Introductionmentioning
confidence: 99%
“… The prevalence of self-reported wheat allergy; ( A ): the subgroup analysis for age; ( B ): the subgroup analysis for economy; ( C ): the subgroup analysis for region, ( D ): the subgroup analysis for timespan [ 18 , 19 , 21 , 23 , 26 , 27 , 28 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 41 , 42 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 59 , 62 , 63 , 66 , 67 , 68 , 70 , 71 , 72 ]. …”
Section: Figurementioning
confidence: 99%